Effects of Aging Temperature on Microstructure and Thermal Properties of CuAlMn Shape Memory Alloys - Canbay, Canan Aksu; Güdeloğlu, Samet (My University, 2017)
The use of copper-based shape memory alloys is increasing rapidly. In this study, the aging effects of CuAlMn shape memory alloys were investigated. Three different alloys were produced during the work. These alloys were then aged for one hour at temperatures of 200 ° C, 300 ° C, 400 ° C and 500 ° C. DSC, XRD and microstructural investigations were carried out on samples which were not aged and aged at different temperatures. Experiments have shown that aging at high temperatures has an adverse effect on shape memory effect on alloys.
Keywords: Fizik; Atomik ve Moleküler Kimya; Malzeme Bilimleri; Özellik ve Test; Fizikokimya